Desempenho em leitura, consciência fonológica e nomeação rápida: estudo com alunos do 1º ano do Ensino Fundamental - Neves, Maíza de Miranda (2019)
This research aimed to verify relations among initial manifestations of reading and writing, phonological awareness skills and fast naming, in a group of children starting first year of elementary school. Twenty children from the private education from Itapecerica da Serra participated in the study. The average age of the group was 6 years and 4 months. The procedure consisted in the application of a collective writing task, as well as the application of single words reading tasks, phonological awareness and rapid naming. The data was scored and submitted to statistical tests. The results of Person's correlations lead us to conclude that reading performance is associated to writing. Furthermore, the results suggest that reading and writing are associated to components of phonological awareness: rhyming skills and phonemic deletion. Besides, reading is associated to rapid naming as well as phonological awareness also shows being related to rapid naming. Clusters results showed us all children’s performance and where they are according to their development in the tasks